Absolute Quantum Yields In Photocatalytic Slurry Reactors - Brandi, Rodolfo Juan (2003)
Photocatalysis in slurry reactors have the particular characteristic that the reacting medium not only absorbs but also scatters photons and both phenomena occurs simultaneously. When this is the case, typical methods used in classical photochemistry such as homogeneous actinometry are useless because they cannot take into account radiation scattering. Consequently present methods in use always underestimate quantum yields calculations. A method has been developed to produce absolute values of photocatalytic quantum yields in slurry reacting systems employing titanium dioxide and near UV radiation. The new procedure resorts to the rigorous solution of the radiative transfer equation inside the reaction space in order to obtain the true value of the photonic absorption rate. Employing monochromatic light, values for the photocatalytic decomposition of phenol and 1,4-dioxane are reported under precisely defined conditions. The method can be used to compare reactivities of different catalysts or, for a given catalyst, reactivities with different compounds regardless the reactor shape, size or configuration.